Doctrine of informed consent in healthcare: its Current practice in Malaysia / Norhani Nordin, Nornadia Muri and Nurul Najwa Zainuddin. - Nordin, Norhani; Muri, Nornadia; Zainuddin, Nurul Najwa (Faculty of Law, 2007)
The main objective for this Honours Project Paper is to unearth the application of the doctrine of informed consent in healthcare and its application in Malaysia. Apart from that, we also highlighted several landmark cases and also developments of this doctrine in other countries including United Kingdom, Australia and United States of America. We also enlighten our readers with the significance of this doctrine so that they would know what their rights are when it comes to the negligence of their physician in informing them the nature and inherent risks in the proposed treatment. This doctrine has developed tremendously in the western countries therefore, it is important for us to keep abreast of its development.